2017
DOI: 10.1016/j.mre.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

First experimental comparisons of laser-plasma interactions between spherical and cylindrical hohlraums at SGIII laser facility

Abstract: We present our recent laser-plasmas instability (LPI) comparison experiment at the SGIII laser facility between the spherical and cylindrical hohlraums. Three kinds of filling are considered: vacuum, gas-filling with or without a capsule inside. A spherical hohlraum of 3.6 mm in diameter, and a cylindrical hohlraum of 2.4 mm × 4.3 mm are used. The capsule diameter is 0.96 mm. A flat-top laser pulse with 3 ns duration and up to 92.73 kJ energy is used. The experiment has shown that the LPI level in the spherica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Thus, the particular profiles of different species plasmas will be formed along the path of an inner-ring laser propagation. Chen et al researched the parametric instabilities in gas-filled hohlraums with a capsule, and compared the simulated results with experimental data in the SGIII laser facility [21]. They found that the plasma waves were strongly damped and the SRS was mainly developed at plasma conditions of electron density from 0.08n c to 0.1n c .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the particular profiles of different species plasmas will be formed along the path of an inner-ring laser propagation. Chen et al researched the parametric instabilities in gas-filled hohlraums with a capsule, and compared the simulated results with experimental data in the SGIII laser facility [21]. They found that the plasma waves were strongly damped and the SRS was mainly developed at plasma conditions of electron density from 0.08n c to 0.1n c .…”
Section: Introductionmentioning
confidence: 99%